2007
DOI: 10.1002/qsar.200740123
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Furo[2,3‐b]pyrazine Nucleoside Analogues with 1,2,3‐Triazole Linkage

Abstract: Sonogashira coupling reaction with the readily available 1-(4-methoxybenzyl)-3,5-dichloropyrazin-2(1H)-ones was followed by mild silver-catalyzed cyclization to provide the corresponding 2-chlorofuro[2,3-b]pyrazines in excellent yields. A second Sonogashira cross-coupling reaction resulted in the formation of 2-ethynylfuro[2,3-b]pyrazines, which were coupled with d-ribose and 2-deoxy-d-ribose using a microwave-assisted Cu(I)-catalyzed Huisgen [2 þ 3] dipolar cycloaddition reaction, to generate a small library … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Similar systems have been reported in which furo [2,3-b]pyrazines are linked to the sugar moiety by means of a triazole bridge [62]. In this case Cu(I) has been produced in situ from Cu(0) and CuSO 4 , N,N,N-tris[(1-benzyl-1H-1,2,3-triazol-4-yl)methyl] amine (TBTA) has been used as the ligand for Cu(I).…”
Section: Nucleoside and Nucleotide Triazole Derivatives And Analoguesmentioning
confidence: 55%
“…Similar systems have been reported in which furo [2,3-b]pyrazines are linked to the sugar moiety by means of a triazole bridge [62]. In this case Cu(I) has been produced in situ from Cu(0) and CuSO 4 , N,N,N-tris[(1-benzyl-1H-1,2,3-triazol-4-yl)methyl] amine (TBTA) has been used as the ligand for Cu(I).…”
Section: Nucleoside and Nucleotide Triazole Derivatives And Analoguesmentioning
confidence: 55%
“…In the same manner, Ermolat’ev et al 14 (Scheme 6) and Broggi et al 15 (Scheme 7) showed that the Huisgen 1,3-cycloaddition can be completed in high yield in only few minutes using microwave irradiation.…”
Section: Nucleosidesmentioning
confidence: 84%
“…The same authors evaluated the coupling of a set of newly generated furo [2,3-b]pyrazines with five-membered sugars [88] using a microwave-assisted regioselective Cu I -catalysed [2+3] dipolar cycloaddition reaction. A small library of hitherto unknown nucleoside analogues was generated (Scheme 65).…”
Section: C-n Bond Formations By Click Chemistrymentioning
confidence: 99%